Coulomb explosion imaging of polyatomic molecules after photoionization with X-rays and strong laser fields - Ablikim, Utuq (Kansas State University, 2017)
Imaging the structures of molecules, understanding the molecular dynamics in onization and dissociation processes and, most importantly, observing chemical reactions, i.e. the making and breaking of chemical bonds in real time, have become some of the most exciting topics in the atomic and molecular physics. The rapid advances of experimental tools such as synchrotron radiation light sources, free-electron lasers and continuing advances of tabletop femtosecond ultrashort lasers that provide laser pulses at a variety of wavelengths have opened new avenues for understanding the structure of matter and the dynamics of the chemical interactions. In addition, significant improvements in computational techniques and molecular dynamic simulations have provided complementary theoretical predictions on structures and chemical dynamics. The Coulomb explosion imaging method, which has been developed and applied in many studies in the last three decades, is a powerful way to study molecular structures. The method has mostly been applied to small diatomic molecules and to simple polyatomic molecules. In this thesis, Coulomb explosion imaging is applied to study the structure of isomers, molecules that have the same chemical formula but different chemical structures. Specifically, by taking inner-shell photoionization as well as strong-field ionization approaches to ionize and fragment the molecules and by using coincidence electron-ion-ion momentum imaging techniques to obtain the three-dimensional momentum of fragment ions, structures of isomers are distinguished by using the correlations among product ion momentum vectors. At first, the study aims to understand if the Coulomb explosion imaging of geometrical isomers can identify and separate cis and trans structures. Secondly, in order to extend the application of the Coulomb explosion imaging method to larger organic molecules to test the feasibility of the method for identifying structural isomers, photoionization studiesof 2,6- and 3,5-difluoroiodobenzene have been conducted. In addition, using the full three-dimensional kinematic information of multi-fold coincidence channels, breakup dynamics of both cis/trans geometric isomers and structural isomers, and in particular, sequential fragmentation dynamics of the difluoroiodobenzene isomers are studied. Furthermore, for each study, Coulomb explosion model simulations are conducted to complement the experimental results. The results of the Coulomb explosion imaging reseach in this thesis paves the way for future time-resolved Coulomb explosion imaging experiments aiming to understand the transient molecular dynamics such as photoinduced ring opening reactions and cis/trans isomerization processes in gas-phase molecules.
Keywords: Coulomb explosion imaging; Velocity map imaging; cis trans isomers; Coincidence Imaging; Channel-resolved photo-electron spectroscopy; X-ray synchrotron